Don't words come easy? A psychophysical exploration of word superiority - Starrfelt, Randi; Petersen, Anders; Vangkilde, Signe (Frontiers in Human Neuroscience, 2013)
Words are made of letters, and yet sometimes it is easier to identify a word than a single letter. This word superiority effect (WSE) has been observed when written stimuli are presented very briefly or degraded by visual noise. We compare performance with letters and words in three experiments, to explore the extents and limits of the WSE. Using a carefully controlled list of three letter words, we show that a word superiority effect can be revealed in vocal reaction times even to undegraded stimuli. With a novel combination of psychophysics and mathematical modelling, we further show that the typical WSE is specifically reflected in perceptual processing speed: single words are simply processed faster than single letters. Intriguingly, when multiple stimuli are presented simultaneously, letters are perceived more easily than words, and this is reflected both in perceptual processing speed and visual short term memory capacity. So, even if single words come easy, there is a limit to the word superiority effect.